The validity and utility of combining ultrasonography with different clinical scores in diagnosis of acute appendicitis - Agarwal, Ritika; Agarwal, Abhinav; Kumar, Ashvini; Kumar, Mukesh (International Surgery Journal, 2019)
Background: There are no controlled studies combining the use of either of the scores- Modified Alvarado, RIPASA or AIRS with ultrasonography. This study was conducted to evaluate the diagnostic accuracy of the existent clinical scoring systems in combination with ultrasound imaging in the diagnosis of acute appendicitis in our patients. Methods: All patients with clinical diagnosis of acute appendicitis and who underwent emergency appendectomy were included in the study. A detailed history of presenting illness was elicited and clinical examination, relevant blood investigations and abdominal ultrasonography were done. All patients were scored according to MAS, RIPASA and AIRS. Histopathology was taken as the gold standard. Results: The study included 118 patients. From our study population, 107 had acute appendicitis on histopathology. There was no statistically significant difference between the accuracy of MAS and RIPASA and both were equally good in diagnosing acute appendicitis as far as the diagnostic accuracy is concerned. Combined MAS, Combined RIPASA and Combined AIRS were obtained after combining ultrasonography findings with MAS, RIPASA score and AIRS respectively. The diagnostic accuracy, sensitivity, specificity, PPV and NPV for Combined MAS were 96.6%, 99.1%, 72.7%, 97.2% and 88.9% respectively, for combined RIPASA were 95.8%, 99.1%, 63.6%, 96.4% and 87.5% respectively and for combined AIRS was 96.6%, 99.1%,72.7%, 97.2%, 88.9% respectively. Conclusions: If ultrasonography is used in conjunction with current clinical scoring systems then the diagnostic accuracy is enhanced. Therefore, USG should be done in all cases being evaluated for acute appendicitis; irrespective of the score being used.